Balance ninja: towards the design of digital vertigo games via galvanic vestibular stimulation - Byrne, Richard; Marshall, Joe; Mueller, Florian ‘Floyd’ (2016)
Vertigo – the momentary disruption of the stability of perception – is an intriguing game element that underlies many unique play experiences, such as spinning in circles as children to rock climbing as adults, yet vertigo is relatively unexplored when it comes to digital play. In this paper we explore the potential of Galvanic Vestibular Stimulation (GVS) as a game design tool for digital vertigo games. We detail the design and evaluation of a novel two player GVS game, Balance Ninja. From study observations and analysis of Balance Ninja (N=20), we present three design themes and six design strategies that can be used to aid game designers of future digital vertigo games. With this work we aim to highlight that vertigo can be a valuable digital game element that helps to expand the range of games we play.